Cascade Filtration With PCR Detection and Field-Flow-Fractionation Online With ICP-MS for the Characterization of DNA Interaction With Suspended Particulate Matter - Nischwitz, Volker; Stelmaszyk, Lara; Piel, Sandra; Tiehm, Andreas (Frontiers in Chemistry, 2022)
The variety of applied antibiotics in animal and human medicine results in the release, development, and spread of relevant numbers of antibiotic resistance genes (ARGs) in the environment. The majority of ARGs are present in intracellular forms (in bacteria). Neglected aspects are extracellular variants of ARGs (eARGs) and their fragments, which have been detected in surface-water samples and sediments. The stability of eARGs is expected to be low; however, binding to particulate matter is likely to improve their stability and also affect their transport and dissemination behavior. Few studies have investigated DNA particle interactions, mostly via indirect characterization of adduct formation in model systems but not in real environmental matrices. Therefore, our study aims at a novel approach for direct characterization of desoxyribonucleic acid (DNA) particle interactions using both cascade filtration and field-flow fractionation. Cascade filtration with quantitative polymerase chain reaction (qPCR) detection indicated retention of ARGs on filters with much larger pore sizes supporting the hypothesis of ARG-particle interactions. However, artifacts from membrane clogging or DNA–membrane interaction cannot be excluded. Consequently, asymmetric flow field-flow fractionation was investigated as an alternative separation technique with the advantage of particle separation in a thin channel, reducing the risk of artifacts. The key method parameters, membrane composition, molecular weight cut off, and carrier composition, were systematically investigated using a calf-thymus DNA-spiked surface-water sample as a model. The results clearly showed a shift in the elution time of clay particles suggesting the presence of DNA–clay adducts. Multi-element detection by inductively coupled plasma mass spectrometry (ICP-MS) enabled monitoring of clay via the Al, Fe, and Si signals and DNA via the P signal. Matching peak profiles for the new fraction in the fractograms of the ARG and DNA-spiked water sample support adduct formation. Further evidence was provided by a novel post-channel filtration approach for the separation of free DNA from DNA–clay adducts.